To study the association between SCC and bacteria numbers and milk composition in farm bulk milk supplied to Tui Milk Products Company for 1992/3 season : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science at Massey University - Ntim, Joseph Osei (Massey University, 1995)
The association between bulk milk SCC and bacteria numbers and milk composition were studied using data containing test records of 12OO farms which supplied bulk milk to TUI Milk Company Limited, for 1992/93 season. Three data sets were created, (1) data set A (N = 4623) with all measurements recorded for each herd for the same milk sample; (2) data B (N = 30 120) with all measurements of BMSCC and milk composition recorded for each herd within a 10 day period but not necessarily on the same sample of bulk milk; and (3) data set C (N = 33 800) with all measurements of bulk milk bacteria numbers and milk composition recorded for each herd within a 10 day period but not necessarily on the same sample of bulk milk. Correlation was used to determine the association between bulk milk SCC and bacteria numbers and milk composition. Multiple regression analysis was also carried to determine the association between bacteria numbers (dependent variable) and SCC and milk composition for early lactation and whole lactation. The results showed the overall average of the mean BMSCC of 280 000 cells/ml of all the farms studied. Approximately 85 % of the farms supplied bulk milk with SCC <250 000 cells/ml, while 1 % of the farms supplied bulk milk with SCC >5OO OO0 cells/ml. Both bulk milk SCC and bacteria numbers were higher in early and late parts of lactation. Highly significant but low positive corretations occurred between the mean bulk milk SCC and bacteria number in early (r = o.24; r2 = 0.06; P<0.001) and whole lactation(r = 0.15; r2 = 0.02; p<0.001). Thus 2 to 6 % of the variation observed in bacteria count was accounted for by variation in bulk milk SCC.The mean fat %, protein % and total solids % increased from mid-lactation to the end of lactation. In contrast, the mean lactose % showed a decrease as the lactation progressed. On the average for the whole lactation, low positive correlations occurred between the mean bulk milk SCC and fat % (r = 0.18), protein % (r = 0.26) and total solids % (r = 0.15). However, a moderate but highly significant negative correlation occurred between bulk milk SCC and lactose %(r= -0.43; P<0.001). In conclusion the overall low average BMSCC suggests that good quality bulk milk was supplied to the company, which also meets the EC standards. Significant low correlation between BMSCC and bacteria numbers suggests that mastitis bacteria were only a small but significant contributor to the high bacteria count in the bulk milk particularly in early lactation, with dirty milking machines or poor cooling being the most likely major contributor. Finally, lactose % was more sensitive to mastitis effective than fat %, protein % and total solids % in the bulk milk.
Keywords: Microbiology; Milk; Milk Quality; New Zealand